An analysis of elementary students' ecological literacy growth within science project-based learning - Sarah Fazilla; Yulia Santi; Annisaturrahmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Ecological literacy is not only environmental knowledge but also a critical mindset that integrates science, ethics, and action. This mixed-method analysis analyzes the ecological literacy skills of PGMI students in the science course through project-based learning (PBL). Data were collected through tests, interviews, and observations, then analyzed quantitatively and qualitatively using a triangulation approach. Test results indicated strong performance on indicators of ecological knowledge, systematic thinking, ecological empathy, and critical-evaluative thinking, but only adequate performance on the action indicator. These findings align with the interviews and observations: the majority of prospective teachers possess good ecological knowledge, as evidenced by PjBL projects that use eco-friendly materials and demonstrate adequate critical thinking, yet concrete actions in the environment remain underdeveloped. The recommendations of this study are to strengthen community-based campus programs, such as environmental internships and collaborations with elementary schools, to implement concrete actions, so that ecological literacy has a tangible impact on the community and learning in elementary schools.